2016
DOI: 10.1371/journal.pone.0165244
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Research Activity in Gastroenterology: Pancreatitis Is in Real Danger

Abstract: ObjectiveBiomedical investment trends in 2015 show a huge decrease of investment in gastroenterology. Since academic research usually provides the basis for industrial research and development (R&D), our aim was to understand research trends in the field of gastroenterology over the last 50 years and identify the most endangered areas.MethodsWe searched for PubMed hits for gastrointestinal (GI) diseases for the 1965–2015 period. Overall, 1,554,325 articles were analyzed. Since pancreatology was identified as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Since 2003, the National Institutes of Health (NIH) budget for digestive disease research has plateaued, while corporate funding for gastroenterology research has dropped by more than 60% since 2008. [ 19 , 20 ] This translates into increased competition for grant applications, which are being awarded at the lowest rate in decades. [ 21 ] RCTs are among the most time-consuming and expensive research studies, but they produce the highest level of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2003, the National Institutes of Health (NIH) budget for digestive disease research has plateaued, while corporate funding for gastroenterology research has dropped by more than 60% since 2008. [ 19 , 20 ] This translates into increased competition for grant applications, which are being awarded at the lowest rate in decades. [ 21 ] RCTs are among the most time-consuming and expensive research studies, but they produce the highest level of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…It is the most common gastrointestinal cause of hospitalization [1], associated with high financial burdens [2]. Several studies have shown that the incidence of AP is increasing [3,4], probably as a result of a combination of risk factors, such as obesity and gallstone disease [5]. The overall mortality rate is 3% to 10%, but patients with the severe form of the disease are at an increased risk of death, with a mortality rate of 36% to 50% [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Szentesi et al провели анализ активности исследовательской работы в области гастроэнтерологии и отметили, что исследования по панкреатитам проводятся все реже (рис. 5) [33] The article presents a detailed review of the research results in the field of pancreatology published in 2018. Certain parts of the review are devoted to the pathogenesis, diagnostics, course of pancreatitis, its treatment, as well as autoimmune, hereditary pancreatitis, pancreatic pathology in children, as well as treatment.…”
Section: заболевания пж у детейmentioning
confidence: 99%